Manfaat Sharing Pengalaman Mengajar Dalam Forum KKG Bagi Peningkatan Kompetensi Guru SD Dalam Mengajarkan IPA - Jumrodah, Jumrodah (LP2M IAIN Palangka Raya, 2010)
A good teaching-learning process can only be done by qualified teachers with adequate teaching competency in terms of planning and managing teaching and learning activities, and assess student learning outcomes. Therefore, teachers are required to master a set of knowledge and teaching skills. This study aims to determine the benefit of sharing teaching experience in the KKG forum for the improvement of teacher competence in teaching science (IPA) in primary schools. The competence of teachers here are focused on opening and closing skills and mastery of the lessons concepts. The method used is an experiment conducted in 7 primary schools in the cluster environment of Gugus Wiyata Bhakti, Cisurupan, Garut District. The results of analysis on observing the teachers showed that after attending the sharing of teaching experience in the KKG forum teachers skills of opening and closing capabilities are getting better with bringing forward all aspects of opening and closing the lesson. Also the tests analysis indicated that teachers mastery on the concept showed that the N-Gain is 0:36 with medium category.